Estriol induced squamous metaplasia on the nasal mucosa in patients with hereditary hemorrhagic telangiectasia - Sadick, Haneen; Bergler, Wolfgang F.; Oulmi-Kagermann, Jasmina; Naim, Ramin; Sadick, Maliha; Hörmann, Karl; Riedel, Frank (Archives of medical research, 2005)
Background - The aim of this study was to evaluate by light and electron microscopy the effect of topical estriol on the nasal mucosa in patients with hereditary hemorrhagic telangiectasia (HHT). - Methods - Twelve patients were instructed to apply twice daily 0.1% estriol as a nose ointment over a period of 12 months. Written consent was obtained from each patient, allowing biopsy specimens of the nasal mucosa to be taken prior to and 3, 6 and 12 months after estriol application. - Results - Metaplastic change of the nasal mucosa was observed 6 months after topical estriol application. The former ciliated columnar epithelium changed into a keratinizing squamous epithelium. The effect was reversible after discontinuation of estriol application. - Conclusions - For the first time, we could outline the effect of topical estriol on the nasal mucosa. These histomorphological findings, and the fact that estriol is a low-potency metabolite of estradiol, make estriol a valuable agent in the treatment of HHT patients.